2013
DOI: 10.1002/oa.2312
|View full text |Cite
|
Sign up to set email alerts
|

Early Pig Management in the Zagros Flanks: Reanalysis of the Fauna from Neolithic Jarmo, Northern Iraq

Abstract: In this paper, we present a reanalysis of pig (Sus scrofa) remains from the Neolithic site of Qalat Jarmo, originally excavated in the 1940s and 1950s. Employing modern zooarchaeological techniques, not available during the initial analyses, we explore the nature of swine exploitation strategies and demonstrate that pigs were most likely managed by the early 7th millennium (Pottery Neolithic) and perhaps earlier. Comparing biometric data with those from other sites in the region, we show that the Jarmo pigs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…At the PPN-PN transitional site Jarmo, where Sus scrofa represent less than 10% of the fauna, small-sized domesticates appeared by around 7000 cal. BC at the latest (Flannery 1983;Price and Arbuckle 2015).…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%
“…At the PPN-PN transitional site Jarmo, where Sus scrofa represent less than 10% of the fauna, small-sized domesticates appeared by around 7000 cal. BC at the latest (Flannery 1983;Price and Arbuckle 2015).…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%
“…
Figure 6.Comparison of the measurements taken on Suidae tibiae and astragali to long term changes in size shown by Price and Evin (2019) to include the Asiab data from the new excavation in black with white central dot and that published by Bökönyi (1977) in grey.
Figure 7.Comparison of the LSI of wild boar and domestic pig bones from sites across the Zagros. Modified from Price and Arbuckle (2013) from original data published by Meadow (1983), Bökönyi (1977), Turnbull (1983), Lasota-Moskalewska (1994), Stampfli (1983) and Turnbull and Reed (1974). The small bones from Nemrik 9 may have been juvenile.
…”
Section: Suidae: Wild or Domesticatedmentioning
confidence: 99%
“…These results suggested a gradual intensification of the relationship between humans and Suidae, with most of the animals neither fully wild nor fully domestic, but managed livestock probably still breeding with wild animals. Price and Arbuckle (2013) have recently reanalysed the Suidae remains from Jarmo and concluded that that there is evidence for the early management of domesticated pigs in the Pre-Pottery Neolithic (PPN), whereas earlier publications (Flannery 1983; Reed 1960; Stampfli 1983) have suggested that domestication occurred later in the sequence in the Pottery Neolithic (PN). The frequency of Suidae at Jarmo varied between 2 and 7 per cent and after some of the bones from PN levels were reassigned to the PPN levels, Price and Arbuckle (2013) suggested that the presence of smaller animals in the PPN layers also demonstrated the presence of managed pigs at an intermediate stage of domestication in the earlier phases of the settlement.…”
Section: Suidae: Wild or Domesticatedmentioning
confidence: 99%
“…Zeder's work (2001, Zeder and Hesse, 2000 on museum collections has resulted in a high resolution understanding of the timing and processes of goat domestication in western Iran and mapped the diffusion of domestic sheep into the EFC, while the recent reanalysis and dating of the pig remains from Qalat Jarmo has clarified the spatio-temporal patterns of the emergence of pig husbandry in the region (Price and Arbuckle, 2015). The situation for cattle, however, has not been similarly reassessed with Flannery's (Hole et al, 1969) work from the 1960s representing the most recent regional synthesis of evidence for cattle domestication in the EFC (see also Reed, 1960).…”
Section: Bos Exploitation In the Eastern Fertile Crescent (Efc)mentioning
confidence: 98%
“…A dramatic decline in the body size of both male and female Bos, often used as a proxy for the suite of biological and behavioral changes known as the 'domestication syndrome' associated with domesticated livestock (Arbuckle, 2005;Hammer, 1984;Price, 1984;Zeder, 2012), is first evident at sites along the Turkish Euphrates in the early eighth millennium BC including MezraaTeleilat and Gritille and slightly later at Gürcütepe and Akarçay (SE Turkey) (Peters et al, 2015;Sana and Tornero, 2008) and within a few centuries cattle management is evident along the Syrian Euphrates at Tell Halula (Sana and Tornero, 2013).…”
Section: Domestication Of Taurine Cattle In the Fertile Crescentmentioning
confidence: 99%